Animation graphics in the presentation - Umarkhon Sobitovich Mukhamedov (International Journal on Human-Computing Studies, 2021)
This article covers the basics of working with GIF Animator and Animate Me! With their help, you can create quite interesting animations that can be used in web-design and presentations, giving our work great visibility and individuality. This, of course, increases the effectiveness of the perception of the information conveyed to the right audience. The principles of creating GIF-animation, methods of their optimization, as well as knowledge of the structure of a GIF-file will help us achieve our goals.